ISO 14063 - Ahn, Therese von; Wikström, Charlotte (2005)
The enterprises of today are beginning to realize that environmental issues are a important part of their activity. Companies and organizations are expected to a greater extent communicate their environmental work to the world surrounding them in a trustworthy and structured way. Lack of information or information that is incorrect may bring farreaching consequences. Communication is mentioned in several of the ISO 14001-standards. But what is missing is a guideline how companies should act to create and be sure of the quality of the data that can be used in the environmental communication. There are a lot of report standards but little is said about how the company should conduct their environmental communication. The companies have, many times, not identified their stakeholders to create a picture of what the stakeholders demand. Furthermore, the dialogue with their stakeholders is occurring without planning or any preparation. In the year of 2000, a new ISO standard was created, which was named ISO 14063. It provides a guideline for environmental communication.